THE ROLE AND PLACE OF ADVOCACY IN THE STATE - Рибалко, Гліб Сергійович (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2020)
Introduction. The article is devoted to the issue of determining the role and place of the bar in the state. The urgency of this issue was a consequence of the adoption in June 2016 of the Law of Ukraine "On Amendments to the Constitution of Ukraine (regarding justice)" of 02.06.2016 № 1401-VIII. Summary of the main research results. According to which the Constitution of Ukraine was supplemented by Article 131-2, which stipulates that the bar operates in Ukraine to provide professional legal assistance, and only a lawyer represents another person in court, as well as protection from criminal charges, except in certain cases. Thus, the bar, together with the prosecutor’s office, was included in the justice system. Thus, the bar becomes one of the key elements of the justice system in Ukraine, as the most important constitutional function of the bar is to ensure the right to protection from criminal prosecution and representation of individuals and legal entities in court. By delegating the relevant function of the bar, the state must ensure a high level of professional legal assistance provided by lawyers, which, in turn, has a significant impact on the quality of justice and the exercise of the right to a fair trial. By delegating the relevant function of the bar, the state must ensure a high level of professional legal assistance provided by lawyers, which, in turn, has a significant impact on the quality of justice and the exercise of the right to a fair trial. At the same time, the Constitution of Ukraine provides for the independence of the bar, and the current Law of Ukraine "On Advocacy and Advocacy" generally indicates that the Bar of Ukraine is a non-governmental self-governing institution. Conclusions. The Ukrainian Bar is a professional public association. The National Bar Association of Ukraine is recognized as a non-governmental non-profit professional organization. In turn, the bar is endowed with public law functions, and the inclusion of non-state actors in the system of public power is designed to create an effective mechanism of public control over the activities of the state.